A comparison of student attitudes and perceptions before and after an introductory interprofessional education experience. Issue 1 (January 2014) - Ruebling, Irma; Pole, David; Breitbach, Anthony Paul; Frager, Alfred; Kettenbach, Ginge; Westhus, Nina; Kienstra, Kathleen; Carlson, Judy
Abstract There is increasing acknowledgement that interprofessional education (IPE) holds promise for preparing health professionals as collaborative-ready practitioners. The effects of IPE on learning outcomes are critical in determining the value of such programs. Attitudes are recognized as a significant element in developing behaviors. This study was designed to determine attitudes and perceptions of students toward collaborative learning in an interprofessional context. Three hundred and five students completed a questionnaire regarding attitudes and perceptions toward interprofessional collaboration before and after an introductory IPE course. Also 202 graduating health professional students without IPE completed the same questionnaire. The questionnaire included questions from the University of West England Interprofessional Questionnaire (UWE IQ) and Readiness for Interprofessional Learning Scale (RIPLS). Independent samples t-tests revealed significant positive changes before and after the IPE course for UWEIQ IP-Learning subscale (p = 0.012) and RIPLS (p = 0.05). This study provides some evidence that students who participate in an introductory IPE course early in their professional preparation not only keep positive attitudes toward interprofessional learning, but improve them. As a result, they are expected to be more engaged in learning this important knowledge that should help them to become interprofessional collaborative-ready practitioners.